Studi Farmakognosi, Penapisan Fitokimia, dan Uji Hayati secara BSLT dari Buah Merah (Pandanus conoideus Lam.) - Ratna Djamil; Dian Karina; Wiwi Winarti (Fakultas Farmasi Universitas Pancasila, 2006)
Nowadays Buah Merah (Pandanus conoideus Lam.), the Indonesian herb is famous for medicinal treatment. The chemical constituens of the fruit have been examined, and brine shrimp lethality test (BSLT) have been carried out. On phytochemical screening, the fruit showed the existence of: volatile oil, sterol, triterpene, carrotene, higher fatty acid, flavon aglycon, emodols, coumarine, tannin, steroid glycoside, reducing compound, flavonoside, antosianoside and saponine. Brine Shrimp Lethality Test showed that the LCs of the n-hexane fraction of the fruit was 24.17 ppm, the ethyl acetate fraction was 29.24 ppm, while the methanol fraction was 94.01 ppm. It could be concluded that the n-hexane fraction has the highest biological activity.